Pemanfaatan Gedget dalam Pembelajaran Tatap Muka di SDN 01 Kota Bengkulu - Junesta, Lesty; Juarsa, Osa; Supriatna, Irfan (JURIDIKDAS, 2024)
This study aims to describe the use of gadgets in face-to-face learning in class IVB SDN 01 Kota Bengkulu. This study uses a descriptive qualitative research type. The data collection techniques used are observation, interviews, and documentation with Miles and Huberman data analysis techniques. The results of this study indicate that 1) In the independent curriculum, teachers no longer design learning devices as a whole because they are already available and facilitated by the Minister of Education, teachers only choose several RPPs that are needed and then developed according to the needs of students that have been provided by the government. While the use of gadgets is adjusted to open materials. 2) The school has facilitated the availability of devices such as laptops, laptop chargers, printers, modems, speakers, projectors, mice and projector screens. 3) Carrying out activities in the preliminary activities, the teacher has prepared students and conveyed the learning objectives. In the core activities, the teacher has conveyed the scope of the material, previous learning with the material to be studied. In the closing activities, the teacher has provided reflection and ongoing learning and explained the material at the next meeting. The conclusion of this study is that the use of gadgets in face-to-face learning at SDN 01 class IVB Bengkulu City has been running using independent metrics and the tools needed include laptops, laptop casings, printers, modems, speakers, projectors, mice and projector screens.